PENGARUH YOGA TERHADAP INTENSITAS DYSMENORRHEA PADA MAHASISWI TINGKAT IV PRODI SARJANA KEBIDANAN FAKULTAS ILMUKESEHATAN UNIVERSITAS PASIR PENGARAIAN - Andria, Andria; Nurkhasanah, Siti; Wulandari, Sri; Aroh, Siti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Before and during menstruation, women often experience discoomfort in the lower abdomen or uterine contractions, which is called dysmenorrhea. Dysmenorrhea can be treated with non-pharmacological therapy, namely yoga. Yoga is a form of exercise that reduces pain by relaxing the muscles, soul, mind, and body. The purpose of this study was to determine the effect of yoga on the intensity of dysmenorrhea in Level IV female students of the Midwifery Undergraduate Study Program, Faculty of Health Sciences, Pasir Pengaraian University. This type of research is quantitative research with a Pre-Experimental Research Design with a One Group Pretest-Posttest design. The sample in the study was 20 people. Sampling used the Purposive Sampling technique. Data analysis used the Dependent T test. The results of the analysis showed that there was a change in the intensity of dysmenorrhea pain in 20 respondents. The average NRS scale of respondents before yoga was 4.25 and after yoga was 2.25 with an average before and after yoga was 2,000 with the results of the Dependent T test obtained p value = 0.000 <0.05, this means p value <0.05. So it can be concluded that there is an effect of yoga on the intensity of dysmenorrhea in fourth-year female students of the bachelor Midwifery study program, Faculty of Health Sciences, Pasir Pengaraian University. It is expected that after the study is conducted, respondents can use yoga to treat dysmenorrhea and avoid the use of pharmacological techniques to treat dysmenorrhea.Keywords: Dysmenorrhea , Yoga, NRS Scale